GNE Myopathy: 25 Years After Gene Identification: Facts, Controversies, Enigmas, Prospects - Stella Mitrani-Rosenbaum; Zohar Argov (Journal of Clinical Medicine, 2026)
Twenty-five years after our identification of the genetic defect in GNE Myopathy (GNEM), we review the current state-of-affairs in the research of this unique myopathy. In this narrative review, we describe the clinical aspects of this myopathy, the genetics of this muscle disorder, the biochemistry of the GNE enzyme, and the animal models that have been developed. We critically discuss the accumulating scientific and clinical data that show that hyposialylation cannot be the sole explanation for the disease pathomechanism. The negative or minimal effects of sialic acid supplementation in clinical therapy trials of GNEM call for a re-evaluation of future planned trials. We review the known facts and the current enigmas as well as research controversies in this field. We also discuss the prospects for further basic research, as a reliable animal model of GNEM is lacking, and future genetic therapy of this myopathy.